Current trends and future developments on (bio- ) membranes : membrane processes in the pharmaceutical and biotechnological field - Basile, Angelo (Angelo Bruno); Charcosset, Catherine (Elsevier, 2019)
Current Trends and Future Developments on (Bio- ) Membranes: Membrane Processes in the Pharmaceutical and Biotechnological field presents the main membrane techniques along with their basic principles, mode of operations, and applications. It covers well-known techniques such as ultrafiltration and membrane chromatography, while also exploring emerging membrane technologies which are finding their way in pharmaceutical and biotechnology industries, including membrane emulsification, membrane bioreactors, and solvent-resistant nanofiltration. State-of-the-art applications of membrane systems in areas such as drug delivery and virus removal are also investigated by leading experts in the field. Current Trends and Future Developments on (Bio- ) Membranes: Membrane Processes in the Pharmaceutical and Biotechnological field is a definitive reference for academics, post-graduates, and researchers in the subjects of biochemical engineering, pharmaceutics, and biotechnology. It is also useful to R & D companies and institutions in these areas, specifically those interested in bioseparations, biopurification, bioproduction, and drug delivery.